2013
DOI: 10.1038/pr.2013.235
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype and outcome in infants with hypoxic–ischemic encephalopathy

Abstract: BackgroundAdults with the apolipoprotein E gene (APOE) alleles e4 and e2 are at high risk of poor neurologic outcome after brain injury. The e4 allele has been associated with cerebral palsy and the e2 allele has been associated with worse neurologic outcome with congenital heart disease. This study was done to test the hypothesis that APOE genotype is associated with outcome among neonates who survive after hypoxic-ischemic encephalopathy (HIE).MethodsWe conducted a cohort study of infants who survived HIE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…CP prevalence was also similar between groups. Thus, disability was not associated with APOE genotype among survivors of neonatal HIE 40 .…”
Section: Biomarkers Of Outcomementioning
confidence: 81%
“…CP prevalence was also similar between groups. Thus, disability was not associated with APOE genotype among survivors of neonatal HIE 40 .…”
Section: Biomarkers Of Outcomementioning
confidence: 81%
“…A dermatology clinic in Spain reported that APOE 4 carriers were significantly more frequent in patients with severe psoriasis compared to controls (p = 0.003) and to non-severe psoriasis (p = 0.017). Infants with hypoxic-ischemic encephalopathy did not show an association with APOE allele type [72]. In contrast, the percentage of children with at least one 4 allele was significantly lower in non-Sudden infant death syndrome (SIDS) compared to SIDS (p = 0.016) in a study of infants from Scotland.…”
Section: Co-morbidities In Young Apolipoprotein 4 Carriers (Table 3)mentioning
confidence: 84%
“…Recently, another group of investigators showed that APOE gene and weight at birth are risk factors for future cardiovascular diseases, and these factors seem to be independent factors as well [114]. To note, nonetheless, that these latter findings make the possible mechanistic (molecular) correlations among APOE , cholesterol metabolism, and vascular diseases much less linear than what could have been expected earlier [115,116]. Furthermore, data in support of the interaction between APOE alleles and environment suggest that a specific APOE genotype is a risk factor able to potentiate the toxic effects of various environmental contaminants.…”
Section: Apoe Polymorphism In Normal and Pathologic Conditions Of Thementioning
confidence: 99%